Rekonstruksi Muhammad Abduh Dalam Pembaharuan Pendidikan Islam - Suriadi, Suriadi (AL-WIJDÃN Journal of Islamic Education Studies, 2017)
Among many prominent figures of moslem scientists, Muhammad Abduh is one of the most passionate figures in reforming Islam. The efforts and various concepts of thought Muhammad Abduh indeed need to be appreciated, because the concept of thinking has been able to change the habit of a static society to become more dynamic. The concept of Islamic renewal by Muhammad Abduh can not be separated from the nature and character of the likes of knowledge. The reconstructions of the thought of Muhammad Abduh in the world of Islamic Education are Purification, Reformation, Islamic Defense, and Reformulation. Based on the Four Reconstructions, the educational reform and the reformulation of the law are his ultimate focus. The factors behind the renewal of Islamic education by Muhammad Abduh were social Factors Religion and Education factor Keywords: Muhammad Abduh, Islamic Education Reformulation